Sobreposição em assembleias de aves frugívoras e dispersão de sementes no cerrado Sensu stricto - Silva, Adriano Marcos da (2013)
A range of species eating the same fruit suggests that niche overlap can occur, along with potential competition among them. To test if the overlap in the assemblages of fruit-eating birds in cerrado sensu stricto is larger than would be expected by chance, we performed a comparison with assemblages generated from the use of null models. Five zoochorous plant species were selected and 60 h of focal observation was performed in each one. We recorded species of birds that consumed fruits and the quantity of fruit removed. It was tested if the specialization (d ) varies among the classes of fruit-eating birds. We used an index of Percentage Similarity (PS) between each pair of plant species, using the relative proportion of fruit withdrawn by each bird species according to each fruit species. The mean value of observed PS was compared with the mean PS generated from randomizations. Obligate and partial frugivores were more specialized than opportunistic frugivores (F2,33 = 3.935; p = 0.029). The mean PS observed was 0.1233; the mean PS generated from randomizations was 0.1826. The overlap observed was significantly greater than that expected by the model. This pattern suggests that competition is not an important factor in the formation of the assemblages, occurring the resources share. The abundance of fruits offered, especially in the rainy season, and the small number of frugivorous species exclusively existing in the cerrado may be factors explaining the low influence of interactions and therefore the high overlap between assemblages.